Massive star clusters in high-redshift star-forming galaxies seen at a 100 pc scale thanks to strong gravitational lensing. Issue Volume 12:Issue S316(2015) (31st March 2017) - Dessauges-Zavadsky, Miroslava; Cava, Antonio; Tamburello, Valentina; Schaerer, Daniel; Mayer, Lucio; Richard, Johan; González, Pablo G. Pérez
Abstract: High-resolution imaging reveals clumpy morphologies among z = 1 – 3 galaxies. Most of these galaxies are dominated by disk rotation, which led to conclude that the observed clumps are generated from disk fragmentation due to gravitational instability. Despite the kpc-scale resolution attained by the most advanced facilities and numerical simulations, these clumps are barely resolved at z > 1. Thanks to the stretching and magnification power provided by gravitational lensing, we reach the sub-kpc resolving power to unveil their physics. From our literature compilation of data, we show that without lensing there is a bias toward clumps with high masses and sizes. The high-redshift clumps identified in lensed galaxies have stellar masses 2 orders of magnitude lower and a median size of 250 pc. They resemble local star clusters observed in the most intensively star-forming galaxies. The clump masses and sizes observed in lensed galaxies agree with new simulations, which show that the Toomre instability criterion overestimates the clump masses by a factor of 5 – 6.